The Analysis of Job Satisfaction Nurse Based on Organizational Climate - Nursalam Nursalam; Yety Elina; Erna Dwi Wahyuni (Universitas Airlangga, 2010)
Introduction: Organizational climate is a perception of the organization's members about their organization and it will be able to influence their attitude. Conducive organizational climate is important to improve job satisfaction. Nurse's job satisfaction is needed to increase quality of health service care. The purpose of the study is to analyze the correlation between organizational climate and job satisfaction of nurse.Method: This study was a quantitative research that used a descriptive method with cross sectional survey design. The population was all nurses in IRNA Bedah of RSUD Kabupaten Sampang that consists of 15 people. The sample were 11 people recruited by using purposive sampling. The data was collected by using organizational climate questionnaire and job satisfaction questionnaire, interval scale was used with Likert scoring. The statistic analysis used Spearman's rho and content analysis.Result: The result of the statistic test shows that organizational climate had p = 0.003 which reveals that there was a correlation between organizational climate and job satisfaction of nurse in IRNA Bedah of RSUD Kabupaten Sampang, with r2 = 0.799 (within a range 0.60–0.799). It means that both variable had a strong positive correlation.Discussion: In conclusion, there was a positive correlation between organizational climate and job satisfaction with strong correlation. The writer suggests the next researchers to study dimension of organizational climate from Pines (1982), and factors to influence job satisfaction from McClelland (1962) so that they will be able to compare the correlation between organizational climate and job satisfaction by using another theory.The Analysis of Job Satisfaction Nurse Based on Organizational Climate